Kesetaraan dan Keadilan Gender dalam Bingkai Teologi Hospitalitas Pentakostal - Nunuk Rinukti; Harls Evan R. Siahaan; Agustin Soewitomo Putri (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
Abstract. This manuscript is a study considering to the phenomenon of gender discrimination that still occurs in Christianity. The purpose of this study was to construct the idea of gender equality and justice within the framework of Pentecostal Hospitality Theology. The method used in this research was descriptive analysis and constructive argumentative using literature data related to Hospitality Theology, especially, the Pentecostalism’s response to the issue of gender equality and justice. As a result, Hospitality Theology is a theological construction that expresses openness to all differences equally and fairly. In conclusion, Pentecostal Hospitality Theology cannot be separated from the event of the outpouring of the Holy Spirit. It departs from the narrative virtues of the early church which welcomed different and foreign identities in equality and justice.Abstrak. Naskah ini merupakan sebuah kajian yang memperhatikan fenomena diskriminasi gender yang masih terjadi di kekristenan. Tujuan kajian ini adalah mengonstruksi ide kesetaraan dan keadilan gender dalam bingkai Teologi Hospitalitas Pentakostal. Metode dalam penelitian ini adalah analisis deskriptif dan argumentatif konstruktif dengan menggunakan data literatur yang terkait dengan Teologi Hospitalitas, khususnya sikap Pentakostalisme terhadap isu kesetaraan dan keadilan gender. Hasilnya, Teologi Hospitalitas merupakan konstruksi teologis yang mengekspresikan keterbukaan pada segala perbedaan secara setara dan berkeadilan. Sebagai kesimpulan, Teologi Hospitalitas Pentakostal tidak dapat dilepaskan dari peristiwa pencurahan Roh Kudus dan berangkat dari virtue naratif jemaat mula-mula yang menyambut identitas berbeda dan asing dalam kesetaraan dan keadilan.